Policy on Environmental Law Reform in the Context of Environmental Preservation in Bandar Lampung City - Alfiyan, Angga; Rinova , Dora (Jurnal Ilmiah Hukum dan Hak Asasi Manusia, 2024)
Purpose: The problem is that the development of public green open spaces in Bandar Lampung City has not yet met the proportion requirements in accordance with the applicable Bandar Lampung City Regional Regulations, where there is a minimum standard of 20% of the urban area. Every year, the availability of green open spaces continues to degrade. In 2022, the total availability of green open spaces for the community reached only 4.6%, highlighting the need for policy reforms in environmental law to maintain the community's environment in green open spaces in Bandar Lampung City. Research Methodology: This study uses normative and empirical juridical research methods, employing a qualitative approach with data collection techniques such as literature studies and interviews. Studies have been conducted on related regulations, books, and other literature pertinent to environmental law in society. Results: Implementation of Community Environmental Law Renewal Policy in Green Open Space, an effort carried out by the Regional Government to respond to the minimal availability of Green Open Space for the Community by seeking new green open space alternatives that adapt to zoning to increase healthy air and avoid natural disasters such as droughts, floods, etc., through legal umbrella policies issued by the Regional Government. Limitations: The social and economic factors affecting environmental conservation in Bandar Lampung may not be fully discussed. This aspect is important, because it often becomes an obstacle to policy implementation. Contribution: The article can provide new insights into environmental law reform policies that can be used by policy makers to design or improve policies in Bandar Lampung or other similar areas.